ENHANCING ETHNOMATHEMATICS KNOWLEDGE MEASUREMENT ACCURACY USING MODERN TEST THEORY IN JAMBI PROVINCE - Falani, Ilham; Ramalisa, Yelli; Saputra, Muhammad Adi (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
Ethnomathematics is a potential alternative solution in efforts to preserve culture through the process of cultural integration (ethnography) in mathematics learning. Teachers play an important role in the successful implementation of ethnomathematics. Teachers need to have a deep understanding of the conceptual and practical aspects of ethnomathematics. This knowledge must be known from the start, even when they are still at the stage of becoming prospective mathematics teachers. Therefore, it is important to measure prospective teachers' ethnomathematics knowledge accurately to see the picture of prospective teachers' ethnomathematics knowledge. This research aims to increase the accuracy of measuring the ethnomathematics knowledge of prospective mathematics teachers by comparing several models in the Modern Test Theory approach, which include the Rasch Model, 1, 2, and 3 Parameter Logistics. Data collection was carried out using the Jambi culture-based ethnomathematics test for prospective mathematics teachers with respondents as many as 129 prospective mathematics teachers from Jambi Province. The criteria for the level of accuracy of the model are indicated by the Standard Error Measurement (SEM) and Test Information Function produced by each model. Based on the results of this research, it was concluded that using the Rasch Model produces the best level of accuracy. It is hoped that this research can open new avenues in increasing precision in measuring ethnomathematics knowledge for prospective mathematics teachers.